Non-coding RNAs regulate mitochondrial dynamics in the development of gastric cancer - Chen, Xiatian; Wei, Chuang; Huang, Liting; Syrigos, Konstantinos; Li, Yuzhen; Li, Peifeng (Frontiers in Molecular Biosciences, 2023)
Gastric cancer (GC) is a malignant cancer that reduces life expectancy worldwide. Although treatment strategies have improved, patients with GC still have poor prognoses. Hence, it is necessary to understand the molecular mechanisms of GC and to find new therapeutic targets. Mitochondrial dynamics and mitochondrial dysfunction are associated with cancer cell growth and progression. Numerous studies have reported that noncoding RNAs (ncRNAs) can participate in the occurrence and development of GC by regulating mitochondrial dynamics. Elucidating the crosstalk between ncRNAs and mitochondria would be helpful in preventing and treating GC. Herein, we review and summarize the functions of oncogenes and tumor suppressors in suppressing ncRNAs and regulating mitochondrial dynamics in GC tumor growth, proliferation, invasion and metastasis. This review provides new insights into the pathogenesis of and intervention for GC.